Green rebranding: Regenerative agriculture, future‐pasts, and the naturalisation of livestock. Issue 4 (8th July 2022) - Cusworth, George; Lorimer, Jamie; Brice, Jeremy; Garnett, Tara
Abstract: Anxieties around the relationship between livestock agriculture and the environmental crisis are driving sustained discussions about the place of beef and dairy farming in a sustainable food system. Proposed solutions range from 'clean‐cow' sustainable intensification to 'no‐cow', animal free futures, both of which encourage a disruptive break with past practice. This paper reviews the alternative proposition of regenerative agriculture that naturalises beef and dairy production by invoking the past to justify future, nature‐based solutions. Drawing on fieldwork in the UK, it first introduces two of the most prominent strands to this green rebranding of cattle: the naturalisation of ruminant methane emissions and the optimisation of soil carbon sequestration via the use of ruminant grazing animals. Subsequent thematic analysis outlines the three political strategies of post‐pastoral storytelling, political ecological baselining and a probiotic model of bovine biopolitics that perform this naturalisation. The conclusion assesses the potential and the risks of this approach to grounding the geographies and the temporalities of agricultural transition in the Anthropocene: an epoch in which time is out of joint and natures are multiple and non‐analogue, such that they provide slippery and contested grounds for political solutions. Abstract : Anxieties around the relationship between livestock agriculture and the environmental crisis are driving profound and contentious discussions about the place of beef and dairy farming in sustainable food systems. This paper analyses efforts being made to reposition livestock animals as environmental allies. Under the regenerative agricultural banner, they are framed soil ecosystem engineers whose greenhouse gas emissions are natural and unproblematic.